A secured data hiding using affine transformation in video steganography - Ramalingam, Mritha; Nor Ashidi, Mat Isa; Puviarasi, R. (Elsevier, 2020)
Network security is the most essential aspect of information technology among today’s emerging digital technologies which demands secured communication of information. In this digital network, it is essential to secure the data from intruders and unauthorized receivers. Steganography plays a vital role in secure transmission of data. This paper proposes a steganography method to hide data using affine transformation technique. The secret data are embedded in the coefficients of integer wavelet transform of the video frames. While embedding, the pixel values are distributed using affine transformation. The proposed method has been tested on many input data and the performance is evaluated both quantitatively and qualitatively. The results indicate the enhanced capability of the proposed method that can ensure imperceptible distortions with minimum computational cost in terms of PSNR factor over the existing methods.